When the wind blows hard - Orenstein, Denise Gosliner 1950-; Edwards, Linda 1948- (Reading, Mass. Addison-Wesley, 1982)
After her parents' separation and a subsequent move to Klawock, Alaska, Shawn endures loneliness until her friendship with Vesta and Vesta's grandfather brings new insight into human relationships.
Keywords: Children's stories, American; Divorce -- Fiction; Interpersonal relations -- Fiction; Friendship -- Fiction